Bilingual store names: A contact-linguistic landscape spectacle in Denpasar - Jendra, Made Iwan Indrawan; Wiradnyana, I Made (Politeknik Negeri Bali, 2023)
Drawing upon data from first-hand fieldwork, this study explores the mixing of two different codes that have been recently found to be used as store names in Denpasar, the capital city of the Bali Province, Indonesia. It is aimed at describing the contact-linguistic landscape phenomenon and revealing how local store owners address multilingualism as a response to the increasingly heterogeneous and linguistically hybrid society. The research reviewed related theoretical literatures, applied observation, did some interviews with note takings, from which the data suggest the reason or motivation behind the case. In the study the spotted signages combining Balinese and English words are theoretically resemble intra-lexical code-mixing. The bilingual construction took place because each language is believed to have its own important role: the use of the local tongue reflects motivation to maintain and promote the Balinese cultural and linguistic identity, whereas, the use of English suggests expectation of projecting image of “world class” business therefore has been believed to be a tool of attracting shoppers. Despite the gradual decreasing of its native users over the generation, the option to combining Balinese and English as a business identity in public place mirrors the rising language loyalty among some of the locals that may echo the resistance towards its fatal linguistic loss in the short future.